Coated hard capsules as the pH-dependent drug transport systems to ileo-colonic compartment - Dvořáčková, Kateřina; Rabišková, Miloslava; Muselík, Jan; Gajdziok, Jan; Bajerová, Martina (Drug development and industrial pharmacy, 2011)
PURPOSE: The aim of this study was to investigate the suitability of hard capsules of different composition (gelatin-G, gelatin coated with hydroxypropyl cellulose-G/HPC, and hypromellose-H) for a coating with aqueous dispersion of pH-dependent synthetic polymer Eudragit(®) FS (E(FS)) and to evaluate in vitro the coated capsules as transport systems for ileo-colonic drug delivery. METHODS: Three sets of hard capsules with increasing coating levels (5-30%) were obtained by Wurster technique. The release of model drug (caffeine) from prepared samples was tested using paddle dissolution method with continual pH change (pH 1.2-2 h, 6.8-4 h and 7.5-2 h). RESULTS: During the coating process, no problems occurred and similar suitability of capsules materials for E(FS) application was observed in contrast to some published reports. The application of HPC subcoating onto gelatin capsules surface was shown as the redundant step. The samples G/E(FS)10-15% and H/E(FS)15-20% with 6 h lag time and fast drug release after the pH adjustment to 7.5 corresponded with the requirements for ileic drug delivery. Samples releasing the drug after the pH change to 7.5 in 2-h interval such as G/E(FS) 20%, G/HPC/E(FS) 25% and H/E(FS) 25% are considered as promising transport systems to ileo-colonic area. Samples G/E(FS) 25-30%, G/HPC/E(FS) 30% and H/E(FS) 30% with 7 h lag time could be used for colon delivery. CONCLUSION: The desired intestinal part could be targeted without significant formulation changes only by the selection of capsules shell forming material and suitable E(FS) coating thickness.
Keywords: Hypromellose Derivatives; ileum; kolon; Capsules; Humans; Delayed-Action Preparations; Methylcellulose; Caffeine; methylcelulosa; rozpustnost; želatina; Colon; lidé; deriváty hypromelózy; Drug Delivery Systems; časové faktory; Polymethacrylic Acids; biologický transport; lékové transportní systémy; Gelatin; tobolky; Hydrogen-Ion Concentration; Solubility; léky s prodlouženým účinkem; kofein; kyseliny polymethakrylové; Ileum; koncentrace vodíkových iontů; Time Factors; Biological Transport